(3eLehY aj GdCNdGb hGdBOGH hGdRgO hGdhYXs - (3ESeGYjd Hf Ydj Hf eMehO Hf eMeO Hf YeQ Hf TGgfTGg Hf CjhH(B: (3Gdedc GdeDjO, UGMH MeGI,J (B732 (3g` s ((3aQL Hf eMeO Hf eMeO Hf eMeO Hf eMehO Hf GdSGHb GdJfhNi GdTGaYi GdCSYQi s)
(3ChdgG (B:s
(3bGd ehdGfG GdMeO ddg Pi GdYXeI hGdLdGd hHYO agPG eLehY jTJed Ydi CQHYI aUhd GdaUd GdChd ai JYQja GdNdb s
(3BNQgG (B:s
(3Gddge fhQ OfjGfG HVhA ef Jhajbc hGbWY CjGefG ai GdCJUGd Hc hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B282s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs